Invited review DNA copy number changes as diagnostic tools for lung cancer - Bowcock, Anne M (Thorax, 2014)
Lung cancer usually presents as advanced stage disease and there is a need for early diagnosis so that appropriate treatments can be provided prior to tumour progression. Copy number variation is frequently detected in tumours and can contribute to tumour progression. This is because regions harbouring DNA imbalance can contain genes encoding critical proteins whose altered dosage contributes to the neoplastic process. Three copy number variations (CNVs) from chromosomes 3p26-p11.1 (loss), 3q26.2-29 (gain) and 6q25.3-24.3 (loss) have previously been described in individuals presenting with endobronchial squamous metaplasia. These CNVs were predictors of cancer diagnosed within 44 months with 97% accuracy. An evaluation of this CNV-based classifier with an independent set of 12 samples (10 men and 2 women), each with a carcinoma in situ or invasive carcinoma at the same site at follow-up demonstrated 92% prediction accuracy. The negative predictive value of this classifier was 89%. The gain at 3q26.2-q29 contributed the most to the classification, being present in virtually all lesions. This region harbours the PIK3CA gene and evaluation of the number of copies of this gene gave very similar results to those from array comparative genomic hybridisation. This type of test can be performed on sputum or bronchial brushings. Larger cohorts now need to be examined to confirm this finding and to possibly refine the regions of CNV. This type of approach paves the way for future molecular analyses to assist in selecting subjects with endobronchial squamous metaplastic or dysplastic lesions who might benefit from more aggressive therapeutic intervention or surveillance.